1997 Financial review: BRAC RDP/RCP programme - Kelley, Brian; Pikholz, Lynn (Shorebank Advisory Services, 2016)
1. Opening reflections 2. Portfolio risk management and credit related activities 3. Management and analysis of savings activities 4. BRAG Membership status, issues and trends 5. Branch profitability and RDP financial sustainability analysis 6. Management responsibility and human resource issues 7. Other areas of special donor concern 8. Summary of Shore bank recommendations